Pediatric Functional Constipation: A New Challenge - Samina Khan Bashir; Muhammad Bashir Khan (Advanced Gut & Microbiome Research)
Functional constipation is a common gastrointestinal disorder worldwide in children, adolescents, and adults. Functional constipation is persistent, difficult, and infrequent hard stooling with incomplete rectal emptying that does not have an identifiable cause, such as underlying illness, anatomical abnormality, or medication, and is a diagnosis of exclusion that causes psychological and physical symptoms in the individual. For early identification of functional constipation in children, a physician must exclude organic causes in children by history, physical examination, and lab studies. Multiple complex pathophysiological mechanisms have been linked to childhood constipation, in which stool-withholding behavior is the most common factor. Toilet training along with osmotic laxative use is currently the common therapy for childhood constipation. Despite being a common condition and with novel therapies such as prosecretory agents, neuromodulation, and transanal irrigation modalities, it is challenging sometimes to manage constipation in children. This is due to a lack of knowledge among parents and children about the nature of constipation which causes poor adherence to the treatment and ultimately worsen the condition. The complaint of constipation in a child should not be ignored as early evaluation and treatment is beneficial for the child’s physical and psychological growth. More research is needed to prevent functional constipation in children. This review article highlights the factors responsible for pediatric functional constipation, its management, novel therapies, and challenges to managing this condition.